Time To Put The Shine On Agriculture - New Straits Times, (2008)
Spiralling food prices may be leaving many hungry and even more angry But in every crisis there's an opportunity says agriculture and resource economist Professor Dr Mad Nasir Shamsudin. The dean of UPM's Faculty of Environmental Studies talks to ELIZABETH JOHN about how today s problems could open doors to a more bountiful future.